Acute effects of real and imagined endurance exercise on sustained attention performance - Wieland, Björn; Fleddermann, Marie-Therese; Zentgraf, Karen (Frontiers in Psychology, 2022)
This study investigated acute effects of real and imagined endurance exercise on sustained attention performance in healthy young adults in order to shed light on the action mechanisms underlying changes in cognitive functioning. The neural similarities between both imagined and physically performed movements reveal that imagery induces transient hypofrontality, whereas real exercise reflects both transient hypofrontality effects and the global release of signaling factors (e.g., BDNF or serotonin) due to muscle contraction and the accompanying sensory feedback. We hypothesized improved cognitive functioning after both interventions (imagery and physical endurance exercise) with greater improvements for real exercise because it targets both mechanisms. Fifty-three sport science students completed two 25-min sessions of moderate endurance exercise in either a motor imagery modality or an executed bodily activity within the framework of an order-balanced crossover study. Assessments for sustained attention performance (d2-R) were performed before and after each endurance exercise condition. Statistical results showed improvements for both groups over time, which can mostly be explained by retest effects. However, we observed a significant interaction effect between group and time, F(1.6, 81.9) = 3.64, p = 0.04, η2 = 0.07, with higher increases in the first session in case physical endurance exercise was performed compared to motor imagery exercise, t(51) = -2.71, p = 0.09, d = .75. This might suggest that the release of signaling factors due to muscle contractions with sensory feedback processing is an additional mediating mechanism alongside motor-related transient hypofrontality that improves cognitive performance.